Evaluation of death pathway genes FAS and FASL polymorphisms in chronic HBV infection. (7th April 2013) - Zamani, A. G.; Barlas, I. O.; Durakbasi‐Dursun, G.; Ural, O.; Erdal, E.; Yildirim, M. S.
Summary This study was designed to determine the possible asssociation between selected FAS and FASLG polymorphisms and Hepatitis B virus (HBV) infection. FAS‐670 G/A, FAS‐1377 G/A, FASLG‐844 T/C and FASLG IVS2nt‐124 A/G polymorphisms were genotyped by polymerase chain reaction and restriction fragment length polymorphism (PCR‐RFLP). A total of age and sex matched 108 controls and a hundred chronic HBV patients were recruited to conduct a case–control study. FAS‐670 polymorphism was associated with chronic HBV infection (P = 0.03) FAS‐1377 GG, GA and AA genotypes among the cases (90%, 5% and 5%, respectively) were significantly different from those among the controls (68%, 31.5% and 5.6%; P = 0.00). FASLG‐844 allele distribution was similar between the groups (P = 0.17) but TC genotype (67.3%) was frequent in chronic HBV patients, while CC genotype was found significantly higher (29.6%) in controls. No association between FASLG IVS2nt‐124 polymorphism and chronic HBV infection could be identified (P = 0.55). FAS‐670 polymorphism is associated with chronic HBV infection, while FASLG IVS2nt‐124 A/G polymorphism is not. The FAS‐1377G/A and FASLG‐844 T/C genotypes are likely to play a substantial role in HBV infection. Further studies evaluating polymorphisms in other genes related with apoptosis are needed to elucidate the role of genetic variation in HBV infection.